The Role of ICT and Energy Consumption on Carbon Emissions: An Australian Evidence Using Cointegration Test and ARDL Long-run and Short-run Methodology - Khanal, Avishek (International Journal of Energy Economics and Policy, 2021)
Information and communication technology (ICT) and energy consumption have substantially increased use over the last decade. It has become one of the essential aspects for improving the standard of life for many people. This study investigates the impact of internet use and energy consumption on the carbon emissions (CO2 emissions) using annual data from 1990 to 2019. For this investigation, ADF and PP unit root tests were applied with the Zivot-Andrews structural break for the unit root test. The paper implements the ARDL cointegration test, JJ cointegration test, and Bayer-Hanck test to check the long-run relationship between carbon dioxide emissions (CO2), internet use, and energy consumption with GDP and total population. The cointegration test results show that there exists a long-run relationship between the variables. The long-run findings reveal a negative impact of ICT on the environment, whereas energy consumption has a positive and significant impact on the environment. According to the short-run dynamics results, both internet usage and energy consumption have a positive and statistically significant impact. Thus, the government should increase subsidies and boost the adoption of high-efficiency appliances to lower energy usage. Keywords: ICT, Energy consumption, CO2, Cointegration tests, ARDL, Australia JEL Classifications: O30, Q43, Q54, Q56 DOI: https://doi.org/10.32479/ijeep.11419